Why people think they procrastinate? : a study on adults from Buenos Aires with the general procrastination scale - Fernández Da Lama, Rocío Giselle (2024)
Fil: Fernández Da Lama, Rocío Giselle. Pontificia Universidad Católica Argentina. Facultad de Psicología; Argentina